A conserved domain within Arc1p delivers tRNA to aminoacyl-tRNA synthetases - Simos, Geōrgios; Sauer, Anke; Fasiolo, Franco; Hurt, Ed (Molecular cell, 1998)
Two yeast enzymes that catalyze aminoacylation of tRNAs, MetRS and GluRS, form a complex with the protein Arc1p. We show here that association of Arc1p with MetRS and GluRS is required in vivo for effective recruitment of the corresponding cognate tRNAs within this complex. Arc1p is linked to MetRS and GluRS through its amino-terminal domain, while its middle and carboxy-terminal parts comprise a novel tRNA-binding domain. This results in high affinity binding of cognate tRNAs and increased aminoacylation efficiency. These findings suggest that Arc1p operates as a mobile, trans-acting tRNA-binding synthetase domain and provide new insight into the role of eukaryotic multimeric synthetase complexes.
Elektronische Reproduktion der Druck-Ausgabe 11. April 2001
Gesehen am 02.12.2025